Analysis of plasma 3-methoxytyramine, normetanephrine and metanephrine by ultraperformance liquid chromatographytandem mass spectrometry: utility for diagnosis of dopamine-producing metastatic phaeochromocytoma. (March 2013) - Peitzsch, Mirko; Prejbisz, Aleksander; Kroiß, Matthias; Beuschlein, Felix; Arlt, Wiebke; Januszewicz, Andrzej; Siegert, Gabriele; Eisenhofer, Graeme
Background: Measurements of plasma normetanephrine (NMN) and metanephrine (MN) provide a sensitive test for diagnosis of phaeochromocytomas and paragangliomas (PPGLs), but do not allow detection of dopamine-producing tumours. Here we introduce a novel mass spectrometric based method coupled to ultraperformance liquid chromatography (LC-MS/MS) for measuring NMN, MN and 3-methoxytyramine (MTY), the O-methylated metabolite of dopamine. Methods: Specific collision-induced fragment ions assessed by multireaction monitoring transitions were used for identification, with quantification according to signal intensities of analytes relative to stable isotope labelled internal standards. Results for solid-phase extracted samples from 196 subjects analysed by LC-MS/MS were compared with those analysed by liquid chromatography with electrochemical detection (LC-ECD). Concentration ranges in 125 volunteers were compared with those from 63 patients with PPGLs, including 14 with metastatic disease. Results: The LC-MS/MS method showed linearity over four orders of magnitude with analytical sensitivity sufficient to measure to 0.02 nmol/L. Intra- and inter-assay coefficients of variation ranged from 2.8% to 13.5%. NMN and MN were respectively measured 17% and 10% higher and MTY 26% lower by LC-MS/MS than by LC-ECD. Medians and ranges for 3-methoxytramine, NMN and MN were respectively 0.08 (0.03-0.13), 0.35 (0.13-0.95) and 0.15 (0.07-0.33) nmol/L in volunteers. Among patients with PPGLs, plasma methoxytyramine was six-fold higher in patients with than without metastastases (1.09 versus 0.19 nmol/L) and in three patients was the only metabolite increased. Conclusions: The LC-MS/MS method enables accurate, selective and sensitive measurements of catecholamine O-methylated metabolites that should be particularly useful for screening and management of dopamine-producing metastatic PPGLs.